Rural tourism destination strategy through SWOT analysis in Kg. Kolunsunan, Penampang , Sabah - Fiffy Hanisdah Saikim; Robert Francis Peters; Nattana Simon; Tracy Anak Angk; Awangku Hassanal Bahar Pengiran Bagul (2020)
Kg. Kolosunan is located upstream from Babagon dam in Sabah and currently gazetted as Babagon water catchment area. Since then, human activities on land and river within the vicinity of the dam has since been restricted by local authorities. This has affected local communities’ livelihood that has traditionally depended on farming and river fishing to source for food. Chosen as a pilot project for Payment for Ecosystem Services (PES) since 2015, this project aims to educate and gain support from the local communities to conserve the area. This paper explores the potential(s) of ecotourism in Kg. Kolosunan as an alternative livelihood for the local community which were affected by resource use restriction due to the gazettement of the water catchment area. Data collections were done through survey, in-depth interviews analyzed using SWOT analysis and finally from previous reports. Results showed that the existing ecotourism in Kg. Kolosunan has the potential to be developed as a sustainable ecotourism site. SWOT analysis also identified the requirement management strategies to improve tourism development in Kg. Kolosunan.